2021
DOI: 10.1039/d1gc03128g
|View full text |Cite
|
Sign up to set email alerts
|

Choosing the right strategy: cryogrinding vs. ball milling – comparing apples to apples

Abstract: Despite many reports on ball milling (BM) of chitin, the effect of cryomilling of chitin has not yet been reported, even though it is a solventless and environmentally-friendly method for the processing of chitin polymer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 66 publications
1
7
0
Order By: Relevance
“…All diffractograms showed peaks typically present in α-chitin: 9.24, 12.69, 19.23, 20.58, 23.18, and 26.27°. , Comparing the relative intensities of the crystalline (2θ 19.2°) versus amorphous peak of the same unit (2θ 12.6°) showed that the starting chitin polymer was of approximately the same crystallinity as ChNWs chitin (CrI 95 and 92%, respectively), whereas the peak deconvolution method , (Tables S3–S4 and Figures S12–S13, Supporting Information) demonstrated a CrI of ∼74.9% for the starting material and 69.1% for ChNWs chitin . The peak deconvolution often shows ∼20% lower CrI values than the peak height method, as it was already shown for chitin samples …”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…All diffractograms showed peaks typically present in α-chitin: 9.24, 12.69, 19.23, 20.58, 23.18, and 26.27°. , Comparing the relative intensities of the crystalline (2θ 19.2°) versus amorphous peak of the same unit (2θ 12.6°) showed that the starting chitin polymer was of approximately the same crystallinity as ChNWs chitin (CrI 95 and 92%, respectively), whereas the peak deconvolution method , (Tables S3–S4 and Figures S12–S13, Supporting Information) demonstrated a CrI of ∼74.9% for the starting material and 69.1% for ChNWs chitin . The peak deconvolution often shows ∼20% lower CrI values than the peak height method, as it was already shown for chitin samples …”
Section: Resultssupporting
confidence: 56%
“…The %DA was determined to be ∼82.0 ± 1.5%, for the starting chitin polymer, and 81.4% for ChNWs chitin hence suggesting that no deacetylation took place during hydrolysis. It is, however, known that the empirical calculations using first derivative FTIR differ from "direct" measurements via solid-state cross-polarization magic angle spinning carbon-13 nuclear magnetic resonance ( 13 C CP/MAS-NMR) 84 due to limitations in linearity of the calibration curve in high %DA.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ILs have been exploited to prepare matrices, scaffolds, and composite materials in a form of membranes, microbeads, nanomats, etc. through solution processing techniques [ 66 , 67 ] such as spin-, dip-, or spray-coating, casting, molding, 3D printing, jet wet- and dry-spinning, and electrospinning [ 68 , 69 , 70 , 71 , 72 ].…”
Section: Introductionmentioning
confidence: 99%
“…Figure3. Chitin fibers, membranes, beads, hydrogels, nanomats, and 3D objects prepared through jet wet-and dry-spinning, casting, molding, electrospinning, and 3D printing [74,[79][80][81][82][83]. …”
mentioning
confidence: 99%